(untitled) (Fiep Bulletin - online, 2013)
The metabolic syndrome (MS) represents a clinic disese characterized by a cluster of disease risk fakors related to coronary heart ones and diabetes mellitus type 2. The appropriate food intake has contributed for a better control of the illness. The aim of the study was to relate the glycemic, glycated hemoglobin (HbA1c). Fruits , vegetables and meat intake with th abdominal circumference (AC) in patients with metabolic syndrome in Sinos Vale Region, RS. The study has the descriptive characteristic of 84 patients, being n=37 Male (M) and n=47 female (F), age between 30 and 65, evaluating glicose and HbA1c with 12 hour fasting. The fruit intake, vegetables and meat were usual food inquiry of 24 hours and as support role the food inquiry. Th results obtained were analyzed by means of the Student t Test to find differences of an average (p<0.05). and the Pearson Correlation (programm SPSS 15.0). The measurements showed over the recommended one: CA (p<0.01) in 41% Female and 21% in male, the glycemic (p<0.05) 93% in Female and 64% in Male; the HbA1c was 43% in Female. Concerning the food intake one observed that the average of the daily/portions related to fruits in female were 2 and in male 1,6. The consumption of vegetables daily/portions in female and male were 1,8 and 2 repectively, quite below of the forecast. The results confirm the core fatty relation to the high glycemic and HbA1c in patients with metabolic syndrome and a poor food intake of fruits and vegetables are important because of the bioacive component presence and by the high amountof fibers. The increase of these food intake might be a primary preventive step of metabolic syndrome and coronary heart disease.